Panopticism on The Consumption of Halal Products in Indonesian Muslim Society Markets - Desika, Pratiwi; Ulinnuha, Roma (Journal of Islamic Economic Laws, 2023)
State standardization in realizing the legitimacy of halal products focuses on the rules in Law No. 33 of 2014, which regulate Halal Product Guarantee. The halal label is a sign of the halal statement of a product and a halal guarantee for Muslim consumers in Indonesia. The company’s self-claim on the Halal certification serves as one of the problems besides the issue of habituation. In this vein, Halal certification is designed to control and regulate product halalness in the form of supervision to gain each producer’s acceptance. This article aims to determine the state's role and regulations as a panopticon for producers to register their products to obtain halal certification. The method used in this article is a qualitative approach using library research and the theory panopticon perspective of Michel Foucault to analyze it. The results of this article show that the state and regulations have yet to arrive at the panopticon system in the absence of strong law enforcement. This regulation functions as a monitoring tool for producers by referencing the halal label and its certification printed on the product. The implication of halal certification, a mechanism from internalizing power over every product in circulation to ensure quality and safety in the production process to achieving the status of tested halal, constitutes a more forceful discipline method.